Unlocking Regional Economic Growth: How Industry Sector and Mesoeconomic Determinants Influence Small Firm Scaling - Omar S. López (Economies)
Understanding the drivers of regional economic growth requires examining the mesoeconomic conditions that influence the ability of small firms to scale. This study investigates how the local composition of firms—by size and sector—along with socio-economic and geographic characteristics, affects the prevalence of Scaled Firms across U.S. labor market areas. Using cross-sectional data from 2022, the analysis applies a log-linear regression model to examine the relationship between the density of micro, midsize, and large firms and the share of Scaled Firms (defined as employing 5–99 workers) within industry sectors. Covariates include household wealth, educational attainment, unemployment, population diversity, and metropolitan classification. The results show that the presence of midsize and large firms, along with regional human capital and economic context, is significantly associated with higher levels of small firm scaling. These findings suggest that the mesoeconomic context plays an important role in shaping regional economic growth outcomes and that the composition of local firm ecosystems may influence a region’s capacity for resilience and inclusive development.